Pentingnya Customer Service Terhadap Permintaan dan persepsi Pelanggan Cafe Life Style Hotel Surabaya - Veronika Nugraheni Sri Lestari; Cindy Arivia; Nurmawati Nurmawati; Dwi Cahyono (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2023)
In every consumer decision-making process to purchase a product, the underlying intention of the consumer is to fulfil their needs and desires. Additionally, each consumer has their own unique perception of their choices when selecting a product. Consumer perception is not solely dependent on physical stimuli but also on stimuli related to the surrounding environment and individual circumstances. This engagement activity was conducted at Cafe the Lifestyle Hotel Surabaya. The purpose of this engagement was to analyse consumer activities in the demand and supply conveyed by Cafe the Lifestyle Hotel Surabaya. The engagement employed active participation, observation, interviews, and related documentation methods to obtain valid data and information regarding consumer behaviour. The results of this engagement indicated that the perception of service quality was highly favourable among the visitors of Cafe the Lifestyle. As a result, the visitors felt satisfied and remained loyal. Furthermore, the perception of pricing was positive as the prices offered by the Cafe were deemed appropriate, and the services provided were in line with visitors' expectations.